2004
DOI: 10.1111/j.1399-3038.2004.00197.x
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, single‐blind and crossover study of an amino acid‐based milk formula in treating young children with atopic dermatitis

Abstract: Cow's milk and soy protein allergies are commonly associated with atopic dermatitis (AD) in young children. Amino acid (AA)-based elemental milk formula may improve AD control in these patients. This study investigates the efficacy of AA-based formula in treating young AD patients irrespective of their food allergy status. AD patients younger than 3 yr old were eligible. Sensitization to food allergens was ascertained by skin prick tests and allergen-specific immunoglobulin E (IgE) assay. Patients were then ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 19 publications
0
10
0
2
Order By: Relevance
“…Although not recommended as a direct substitute for cow's milk in sensitized individuals, soy sensitization is relatively uncommon. Our published clinical trial also showed that an amino acid‐based milk formula was not useful in treating AD in young children (15). In the previous study, (6) disease severity did not bear any relationship with the prevalence of sensitization to common food.…”
Section: Discussionmentioning
confidence: 94%
“…Although not recommended as a direct substitute for cow's milk in sensitized individuals, soy sensitization is relatively uncommon. Our published clinical trial also showed that an amino acid‐based milk formula was not useful in treating AD in young children (15). In the previous study, (6) disease severity did not bear any relationship with the prevalence of sensitization to common food.…”
Section: Discussionmentioning
confidence: 94%
“…Two studies blinded participants and outcome assessors (24, 25). Three studies blinded the outcome assessor only (22, 26, 27). In three studies blinding was unclear (19–21).…”
Section: Resultsmentioning
confidence: 99%
“…Elemental diets. Two Elemental diet studies, one cross‐over study (26) and one parallel study (23). The Munkvad study found no significant difference between the two groups for the combined outcome of pruritus, sleeplessness and antihistamine usage (RR 1.69, 95% CI 0.2 to 13.93).…”
mentioning
confidence: 99%
“…Evidence level: B Comments: A systematic review 161 containing 9 RCTs was reported in the Cochrane Collaboration 2008. [332][333][334][335][336][337][338][339][340] Overall, the quality of those RCTs was poor, thus, their evidence level was determined to be low.…”
Section: Cq15 Is the Allergen Elimination Diet Effective For The Trementioning
confidence: 99%